Hypertension in a multi‐ethnic Asian population of Singapore - Gek Cher Chan; Boon Wee Teo; Jam Chin Tay; Chen‐Huan Chen; Hao‐Min Cheng; Tzung‐Dau Wang; Yuda Turana; Kazuomi Kario; Yook‐Chin Chia; Kelvin Tsoi; Guru Prasad Sogunuru; Jennifer Nailes; et al. (The Journal of Clinical Hypertension, 2021)
Abstract The prevalence of hypertension varies by country and region, but it remains a leading yet modifiable risk factor of cardiovascular disease. There are many factors that contribute to the burden of hypertension in Asia, a region with diverse ethnicity. It has been shown that sociodemographic variability is related to ethnic differences, thereby emphasizing the importance of hypertension screening and educating at‐risk or vulnerable groups. In this review, we describe the ethnic differences in genetic variants, dietary choice, and lifestyle habits, as well as its association with sociodemographic differences, hypertension awareness, and treatment control.